2019
DOI: 10.1038/s41467-019-09256-0
|View full text |Cite
|
Sign up to set email alerts
|

Aedes mosquitoes acquire and transmit Zika virus by breeding in contaminated aquatic environments

Abstract: Zika virus (ZIKV) is a mosquito-borne flavivirus that predominantly circulates between humans and Aedes mosquitoes. Clinical studies have shown that Zika viruria in patients persists for an extended period, and results in infectious virions being excreted. Here, we demonstrate that Aedes mosquitoes are permissive to ZIKV infection when breeding in urine or sewage containing low concentrations of ZIKV. Mosquito larvae and pupae, including from field Aedes aegypti can acquire ZIKV from contaminated aquatic syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 45 publications
(61 reference statements)
1
39
0
3
Order By: Relevance
“…Precision of this sample achieved 12%, meaning that target concentration in this sample was between 20 and 26 genomic copies per µL. Experimental ZIKV infection of mosquitoes shows that usually a ZIKV positive mosquito has approximately 10⁴ genomic copies [ 6 ]. The sensitivity of RT-dPCR allows for ZIKV detection with similar sensitivity (≃2.8 × 10⁴) in a pool of 10 mosquitoes, which could represent 2.8 x 10 3 genomic copies per mosquito.…”
Section: Discussionmentioning
confidence: 99%
“…Precision of this sample achieved 12%, meaning that target concentration in this sample was between 20 and 26 genomic copies per µL. Experimental ZIKV infection of mosquitoes shows that usually a ZIKV positive mosquito has approximately 10⁴ genomic copies [ 6 ]. The sensitivity of RT-dPCR allows for ZIKV detection with similar sensitivity (≃2.8 × 10⁴) in a pool of 10 mosquitoes, which could represent 2.8 x 10 3 genomic copies per mosquito.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to understand that the complete sylvatic cycle can be maintained in forests in the presence of vertebrate reservoirs [39]. A recent publication showed that Aedes mosquitoes can also be contaminated with ZIKV by breeding in contaminated aquatic environments [40].…”
Section: Discussionmentioning
confidence: 99%
“…The vector usually breeds in contaminated aquatic environments, for example, stagnant wastewater, and others, thus people living in homes with such breeding sites are prone to mosquito transmission of ZIKV. Aedes mosquito larvae and pupae can acquire ZIKV from contaminated aquatic systems, including urine, resulting in ZIKV infected adult females [73,74]. In contrast with other mosquito species, Aedes mosquitoes are often distributed in urban areas and usually breed in indoor and outdoor settings in a wide variety of natural and artificial waterholding containers such as plastic tanks, cement tanks, flower vases, water storage jars, and rubber tires, among others [75].…”
Section: Determinantsmentioning
confidence: 99%
“…Human social factors may determine ZIKV infection, for example, human density and poverty, among others, are related to higher rates of transmission of Aedesborne pathogens amongst humans [73]. More impoverished African rural areas have lower quality housing and poor drainage, without window screens [74], leading to higher mosquito abundance and biting rates [79]. Besides, population movements among African countries, primarily as refugees, determine the rate of spread of infection into pathogenfree areas [76,77].…”
Section: Determinantsmentioning
confidence: 99%
See 1 more Smart Citation